The effectiveness of buprenorphine for treating cancer pain: an abridged Cochrane review. Issue 3 (15th December 2015) - Schmidt-Hansen, Mia; Taubert, Mark; Bromham, Nathan; Hilgart, Jennifer S; Arnold, Stephanie
Abstract : Objectives: To assess the effectiveness and tolerability of buprenorphine for cancer pain in adults and children. Methods: We searched CENTRAL, MEDLINE, EMBASE, ISI Web of Science, ISI BIOSIS, ClinicalTrials.gov, meta Register of Controlled Trials, WHO International Clinical Trials Registry Platform and the Proceedings of the Congress of the European Federation of International Association for the Study of Pain to early 2015. Results: We included 19 randomised controlled trials comparing buprenorphine with placebo, buprenorphine or another active drug for cancer pain. The trials included 1421 patients and examined 16 different intervention comparisons. Of the 11 studies that compared buprenorphine to another drug, 5, 3 and 3 studies, respectively, found that buprenorphine was superior, no different or inferior to the alternative treatment in side effects profile or patient preference/acceptability. Pain intensity ratings did not differ significantly between intramuscular buprenorphine and buprenorphine suppository, although intramuscular treatment was associated with more adverse events (1 study). One study found faster onset of pain relief after sublingual than subdermal buprenorphine, with similar analgesia duration and adverse event rates. 2 studies found transdermal buprenorphine superior to placebo, whereas a third study found no difference between placebo and different doses of transdermal buprenorphine. No clear dose–response relationship was found for transdermal buprenorphine. The quality of this evidence base was limited by under-reporting, small sample sizes and attrition. Conclusions: Buprenorphine might be considered as a fourth-line option compared with the more standard therapies of morphine, oxycodone and fentanyl, and even then it would only be suitable for some patients.